Identifying, Evaluating and Ranking Effective Factors in Improving the Quality of War Tourism in Iran (Rahyan Noor Travels) - Mohammad Ghasemi; Mohammad Mehdi Mohtadi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Rahyan Noor camps have been considered one example of war tourism in recent decades after the Iran-Iraq war. Due to the importance of this capital, it is worthwhile for the authorities and all the planners of these camps to try to improve the quality of holding these camps. Methodology: This research is a mixed qualitative-quantitative research using the data collection method. This research tries to identify the factors affecting the quality improvement of the Rahyan Noor camps by analyzing the information collected through interviews using the thematic analysis method. Sampling was performed to achieve theoretical saturation. Due to the uncertainty in determining the importance of the factors based on every criterion, ranking is based on the Fuzzy TOPSIS algorithm. Findings: According to the results, optimizing camp time has been selected as the first and most crucial factor, with a relative proximity index of 0.53467. Originality/Value: Optimizing the duration of the camps leads to the appropriate timing of these camps by carefully examining the dispatched groups; the first important step in improving the quality of these camps can be taken according to the desired criteria.